A család ereje: A házasságban élés és a nagycsaládos lét kapcsolata a jóllét különböző mutatóival - FERENCZI, Andrea; KÖVI, Zsuzsanna; MÉSZÁROS, Veronika (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The Strength of the Family: Links between Marital Status, Large Family Structure, and Indicators of Well-Being. THEORETICAL BACKGROUND – Based on previous empirical findings, the relationship between family formation, the number of children, and subjective well-being cannot be considered unambiguous. This complex association is shaped by various individual and social factors. While having children may foster a sense of meaning in life and enrich individuals with emotionally fulfilling experiences, an increasing number of children may, in certain circumstances, strain the stability of family functioning. Regarding the positive consequences of parenthood, religiosity is frequently identified in the literature as a protective factor, and increasing attention has also been given to additional psychological resources – particularly social support and gratitude. GOALS – In this paper, we examine the subjective well-being, perceived social support, and dispositional gratitude of married individuals with large families. The investigation also explores how these psychological phenomena relate to key sociodemographic variables such as age, gender, and religiosity. METHODS – A cross-sectional, quantitative survey was conducted with 809 participants (626 women and 183 men; M_age = 40.8 years, SD = 13.85). The sample included 220 married individuals raising three or more children, while 363 participants reported regularly practising their religion. In addition to providing sociodemographic data, respondents completed the Bern Subjective Well-Being Questionnaire, the GRAT Gratitude Questionnaire, and the Perceived Social Support Questionnaire. RESULTS – The analyses indicated that being married and having a large family was primarily associated with higher levels of perceived social support. Participants in this group reported significantly greater instrumental (t(473.28) = -5.505, p < .001, Cohen’s d = -0.398), emotional (t(472.37) = -5.720, p < .001, d = -0.414), and socially interactive support (t(440.30) = -5.505, p < .001, d = -0.480) compared to individuals in other relational statuses raising fewer children. In contrast, the large-family status did not emerge as an independent shaping factor of subjective well-being when other sociodemographic variables were controlled. A more nuanced pattern emerged for gratitude: marital and large-family status (F = 15.348, p < .001, η² = 0.015), gender (F = 21.764, p < .001, η² = 0.022), and religiosity (F = 64.754, p < .001, η² = 0.065) all showed significant associations with dispositional gratitude. CONCLUSIONS – The findings highlight the complex interplay between gratitude and family as well as religious background. The protective function of dispositional gratitude may be especially relevant for the development of psychological prevention and intervention programmes, as it can contribute both to the enhancement of perceived social support and the maintenance of subjective well-being.